Cervical cancer screening: efficacy of PAX1 and JAM3 methylation assay in the triage of atypical squamous cell of undetermined significance (ASC-US) - Xiaoyan Chen; Haimin Jiang; Hubin Xu; Linhai Wang; Pei Liu; Dongxue Ma; Hui Wang; Huafeng Shou; Xuqian Fang (BMC Cancer)
Abstract Background Atypical squamous cells of undetermined significance (ASC-US) often present diagnostic challenges with cytology-based results, leading to potential underdiagnosis or overdiagnosis. An effective triage method is essential for managing these cases to reduce unnecessary referrals and treatment. Methods A total of 322 women diagnosed with ASC-US were tested for HPV-DNA and the PAX1 and JAM3 methylation (PAX1 m /JAM3 m ) test in the study. Results Methylation levels of PAX1 and JAM3 were significantly elevated in cervical lesions classified as CIN2 or more severe lesions (CIN2+). The methylation assay demonstrated a sensitivity of 83.8% and a specificity of 95.8%, outperforming HPV-DNA testing in differentiating high-grade cervical lesions among women with ASC-US. Moreover, PAX1 m /JAM3 m testing significantly reduced the colposcopy referral rate for further diagnostic procedures in high-risk HPV-positive women by 79.5%. Conclusions PAX1 m /JAM3 m testing shows promise as a reliable supplemental method to HPV-DNA testing for the triage of women with cytologic ASC-US. In addition, the molecular triage based on the CISCER assay or single PAX1 or JAM3 methylation, had better effects in the women with non-HPV16/18 group. This approach could potentially minimize overtreatment and unnecessary referrals in clinical practice, enhancing patient management and resource utilization.